Psychometric Properties of the Make My Day Tool to Assess Perceived Performance of Children ' s Daily Activities - Liron Or; Tsameret Ricon (Scholarworks @ WMU, 2017)
Background: No instrument with strong psychometric qualities exists to measure occupational performance in young children through child-reporting. We investigated the reliability and validity of the Make My Day (MMD) tool for children aged 4 to 7 years and their parents. Method: We administered a demographic questionnaire, the MMD, and two other tools having similar objectives to a sample of 75 typically-developing Jewish-Israeli children aged 4 to 7 years and their parents. For internal consistency, we pooled the data with those from our earlier study involving 62 typicallydeveloping Arab-Israeli children. Results: The MMD exhibited acceptable to good internal consistency for the pooled children's (α = .65 - .89) and parental (α = .68 - .84) data. Paired student's t-testing revealed significantly higher children's self-ratings than parental ratings for performance quality, independence, and performance satisfaction in some activity areas. Factor loadings were of adequate strength, significant, and consistent with the theoretical underpinnings of the tool. The parental version of the MMD exhibits good concurrent validity and good discriminant validity. Conclusion: The MMD has good reliability and validity and, although some aspects remain to be investigated, the MMD is the first self-report tool for children in this age group for which any such data have been reported.